Influence of High Volume RHA on Properties of Cement Mortar. Issue 1 (March 2021) - Al-Khafaji, Zainab S.; Majdi, Ali; Shubbar, Ali A.; Nasr, Mohammed Salah; Al-Mamoori, Shahad F.; Alkhayyat, Ahmed; Al-Rifaie, Ali; Al-Emadi, Nasser; Al-Mufti, Rafal Latif; Sadique, Monower; Hashim, Khalid
Abstract: This work study the impact of partial cement replacement by high volume Rice Husk Ash (RHA) on some characteristics of cement mortar like compressive strength and flexural strength at different ages. In this research, RHA was used in three different ratios (20, 40, and 60)% as a cement substitution and the findings were compared with control mixture (0% RHA). The findings demonstrated that the replacement of cement by RHA reduced the compressive strength of all selected ratios and the increase in the content of RHA lead to reduce compressive strength comparative to control sample with 100% cement as a binder at all ages. However, the flexural strength results indicated that the RHA in 20% showed approximately same results as control sample at early ages while increasing the curing period lead to improve flexural strength. Increasing RHA higher than 20% lead to decrease Flexural strength at all selected ages.